2021
DOI: 10.1099/ijsem.0.004895
|View full text |Cite
|
Sign up to set email alerts
|

Thermococcus henrietii sp. nov., a novel extreme thermophilic and piezophilic sulfur-reducing archaeon isolated from a deep-sea hydrothermal chimney

Abstract: A novel extreme thermophilic and piezophilic chemoorganoheterotrophic archaeon, strain EXT12cT, was isolated from a hydrothermal chimney sample collected at a depth of 2496 m at the East Pacific Rise 9° N. Cells were strictly anaerobic, motile cocci. The strain grew at NaCl concentrations ranging from 1 to 5 % (w/v; optimum, 2.0%), from pH 6.0 to 7.5 (optimum, pH 6.5–7.0), at temperatures between 60 and 95 °C (optimum, 80–85 °C), and at pressures from 0.1 to at least 50 MPa (optimum, 30 MPa). Strain EXT12cT gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Samples from different subsurface settings have been previously used to investigate the abundance, nature, and substrate specific response of deep dwelling organisms via several cultivation-based methods and enrichment studies ( Kotelnikova and Pedersen, 1998 ; Hallbeck and Pedersen, 2008 , 2012 ; Fichtel et al, 2015 ; Rajala et al, 2015 ; Russell et al, 2016 ; Purkamo et al, 2017 , 2020 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ; Imachi et al, 2019 ; Sanz et al, 2021 ; Nuppunen-Puputti et al, 2022 ). The outcome of these studies, resulted in the enrichment of microorganisms mostly belonging to bacterial phyla Proteobacteria, Firmicutes, Actinobacteria, Chloroflexi and Bacteroidetes ( Rastogi et al, 2009 , 2013 ; Fichtel et al, 2012 ; Fortunato and Huber, 2016 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ) and archaeal members including Euryarchaeota, Thaumarchaeota and Crenarchaeota ( Zeng et al, 2009 ; Nuppunen-Puputti et al, 2018 ; Imachi et al, 2020 ; Alain et al, 2021 ; Courtine et al, 2021 ; Li et al, 2021 ). “In the last few years, metagenomic investigations of terrestrial subsurface microbiome” (crustal/vent, faults or fractures fluids, aquifer samples have shown considerable species diversity with potential for assimilation of C and inorganic resources for energy metabolism ( Nyyssönen et al, 2014 ; Purkamo et al, 2015 ; Hubalek et al, 2016 ; Lau et al, 2016 ; Magnabosco et al, 2016 ; Wu et al, 2016 ; Momper et al, 2017 ; Bell et al, 2020 ; Purkamo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Samples from different subsurface settings have been previously used to investigate the abundance, nature, and substrate specific response of deep dwelling organisms via several cultivation-based methods and enrichment studies ( Kotelnikova and Pedersen, 1998 ; Hallbeck and Pedersen, 2008 , 2012 ; Fichtel et al, 2015 ; Rajala et al, 2015 ; Russell et al, 2016 ; Purkamo et al, 2017 , 2020 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ; Imachi et al, 2019 ; Sanz et al, 2021 ; Nuppunen-Puputti et al, 2022 ). The outcome of these studies, resulted in the enrichment of microorganisms mostly belonging to bacterial phyla Proteobacteria, Firmicutes, Actinobacteria, Chloroflexi and Bacteroidetes ( Rastogi et al, 2009 , 2013 ; Fichtel et al, 2012 ; Fortunato and Huber, 2016 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ) and archaeal members including Euryarchaeota, Thaumarchaeota and Crenarchaeota ( Zeng et al, 2009 ; Nuppunen-Puputti et al, 2018 ; Imachi et al, 2020 ; Alain et al, 2021 ; Courtine et al, 2021 ; Li et al, 2021 ). “In the last few years, metagenomic investigations of terrestrial subsurface microbiome” (crustal/vent, faults or fractures fluids, aquifer samples have shown considerable species diversity with potential for assimilation of C and inorganic resources for energy metabolism ( Nyyssönen et al, 2014 ; Purkamo et al, 2015 ; Hubalek et al, 2016 ; Lau et al, 2016 ; Magnabosco et al, 2016 ; Wu et al, 2016 ; Momper et al, 2017 ; Bell et al, 2020 ; Purkamo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among hyperthermophilic archaea belonging to the order Thermococcales , many species of the genus Thermococcus have been isolated from various deep-sea hydrothermal vents. Recently, Thermococcus indicus IOH1 T [8], Thermococcus aciditolerans SY113 T [9], Thermococcus henrietii EXT12c T [10] and Thermococcus camini Iri35c T [11] were isolated from sediment collected from the Central Indian Ocean Ridge (Onnuri vent field), a deep-sea hydrothermal vent chimney on the Southwest Indian Ridge, a hydrothermal chimney on the East Pacific Rise, and a hydrothermal chimney rock sample from the Mid-Atlantic Ridge (Rainbow vent field), respectively.…”
Section: Isolation and Ecologymentioning
confidence: 99%
“…Despite this, pressure seems to be one of the least explored parameters for microbial growth, as relatively few microorganisms from these deep environments have been isolated and/or grown under in situ pressures. To date, fewer than 100 species have been reported to be piezotolerant or piezophilic ( Picard and Daniel, 2013 ; Jebbar et al, 2015 ; Cario et al, 2019 ; Oliver et al, 2020 ; Alain et al, 2021 ; Courtine et al, 2021 ; Li et al, 2021 ; Yu et al, 2021 ; Zhang et al, 2022 ), and few obligate piezophiles have been identified ( Bartlett, 2002 ; Zeng et al, 2009 ). Therefore, our knowledge of active microbial species, their physiological and metabolic potential, and community diversity in these deep environments is limited.…”
Section: Introductionmentioning
confidence: 99%